Co-creating resilient landscapes: transitioning to multifunctional approach in India - Sikka, Alok; Yadav, Shweta; Samaddar, A.; Behera, Abhijit; Tripathi, Mansi; Kumar, Gopal; Mittra, S. (2025)
The CGIAR Multifunctional Landscapes (MFL) Science Program represents a transformative approach to sustainable development, aiming to reimagine rural futures through holistic landscape management that integrates agriculture, environment, nutrition, and policy. As part of the program’s rollout in India, a national consultation titled “Co-creating Resilient Landscapes: Transitioning to a Multifunctional Approach” was convened on 7 August 2025 in Pune, Maharashtra, jointly organized by IWMI and the Alliance of Bioversity International and CIAT. The consultation underscored that building multifunctional landscapes in India demands continuous co-creation across sectors and scales, ensuring biodiversity conservation, climate resilience, and equitable livelihoods within planetary boundaries.